High Out-of-Pocket Health Spending in Countries With a Mediterranean Connection - Grima, Simon; Spiteri, Jonathan V.; Jakovljevic, Mihajlo; Camilleri, Carl; Buttigieg, Sandra C. (Frontiers in Public Health, 2018)
In this study, we analyzed healthcare provision and health expenditure across six Mediterranean countries that adopt the National Health System (Beveridge model) and that form part of the European Union (EU) with the main aim being that of analyzing and comparing out-of-pocket health spending in countries with a European Mediterranean connection. To this end, we considered various economic indicators and statistics to derive commonalities and differences across these countries and also compared trends in these indicators to those observed across the rest of the EU. We then analyzed these findings in light of other data related to the quality of healthcare delivery and the infrastructure of the health system and discussed recent developments in healthcare within each country and the main challenges faced by the respective health systems. The results show that on average, Mediterranean countries spend less on total healthcare expenditure (THE) than the EU average, both as a proportion of GDP, as well as in per capita terms. This is primarily driven by lower-than-EU-average public funding of healthcare. The 2008/2009 macro-economic and financial crisis had a significant impact on the countries under review, and explains the persistent reductions in public health spending as part of the austerity measures put in force across sectors. On the flipside, Mediterranean countries have a higher presence of private health providers in total funding, thereby explaining the higher Out-of-Pocket (OOPs) health expenditures in these countries relative to the EU-average. With regard to the overall health infrastructure in these countries, we observed that although the supply of physicians is largely in line with the rest of the EU, there is under-supply when it comes to hospital beds. This may be symptomatic of lower government funding. Nonetheless, all countries score highly in the evaluation of the quality of health services, as recorded by international rankings like the WHO's 2000 metric, whereas health system performance indicators, namely mortality rates and life expectancy reveal favorable health outcomes in the Mediterranean EU countries. The findings in this paper may be seen in light of the Mediterranean region's lifestyle in terms of diet, health behavior, health beliefs and shared culture. In particular, the higher out-of-pocket expenditure may reflect the tendency for one-to-one relationships with private clinicians and the pursuit of person-centered care (1). Additionally, the Mediterranean people may not be as disciplined as their European counterparts in accessing and using the public health sector. The lower THE also reflects the fact that the Mediterranean countries are less wealthy than the more economically-advanced European countries.